2014
DOI: 10.1039/c4ta01775g
|View full text |Cite
|
Sign up to set email alerts
|

Design of new anode materials based on hierarchical, three dimensional ordered macro-mesoporous TiO2 for high performance lithium ion batteries

Abstract: As anode materials for lithium ion batteries, two three dimensionally ordered macroporous TiO 2 , one with disordered inter-particle mesopores formed by the aggregation of nanoparticles (3DOM) and another with inner-particle mesopores generated by a surfactant templating strategy (3DOMM), have been synthesized using poly(styrene-methyl methacrylate-3-sulfopropyl methacrylate potassium) (P(St-MMA-SPMAP)) spheres as a hard template and their electrochemical properties are compared. SEM and TEM observations revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 63 publications
2
78
1
Order By: Relevance
“…It is known that only a thin layer of a photocatalytic material takes part in the photooxidation reactions, because absorption of UVeVis light is limited by the depth and porosity of material, macro and mesopores network. Several studies showed that the hierarchically macro-mesoporous TiO 2 structures exhibited an important light harvesting effect of the macrochannels allowing light waves to penetrate deeper inside the photocatalyst (Jin et al, 2014). Therefore the porosity of the photocatalytic paint layer and the macromesoporous structure will be important in their photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that only a thin layer of a photocatalytic material takes part in the photooxidation reactions, because absorption of UVeVis light is limited by the depth and porosity of material, macro and mesopores network. Several studies showed that the hierarchically macro-mesoporous TiO 2 structures exhibited an important light harvesting effect of the macrochannels allowing light waves to penetrate deeper inside the photocatalyst (Jin et al, 2014). Therefore the porosity of the photocatalytic paint layer and the macromesoporous structure will be important in their photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that among various nanosized structures the nanoporous architecture has been considered an optimal structure for lithium insertion and extraction [29][30][31] [32,33]. Recently, dealloying was further extended to fabricate the metal oxide nanomaterials [34].…”
Section: Introductionmentioning
confidence: 99%
“…Third, as shown in Fig. 2e, the wrinkled and curved gossamer-like GNSs with high electrical conductivity overcomes the TiO 2 disadvantage of low electrical conductivity, which facilitates lithium insertion/extraction kinetics [28,29]. Forth, the uniform amorphous TiO 2 film reduces path length for Li-ion diffusion and benefits from activation process.…”
Section: Accepted Manuscriptmentioning
confidence: 99%